Increased expression of ATP‐binding cassette transporters in enfortumab vedotin‐resistant urothelial cancer - Mariko Kotono; Toshiki Kijima; Atsuko Takada‐Owada; Naoya Okubo; Ryo Kurashina; Hidetoshi Kokubun; Toshitaka Uematsu; Kohei Takei; Kazuyuki Ishida; Takao Kamai (IJU Case Reports, 2024)
Introduction In addition to reduced nectin‐4 expression, the upregulation of ATP‐binding cassette transporters has been suggested as a potential mechanism of resistance to enfortumab vedotin. Case presentation A 76‐year‐old man previously treated with platinum‐containing chemotherapy and pembrolizumab for metastatic bladder cancer was administered enfortumab vedotin because of disease progression. Subsequently, metastasectomy was performed for oligometastatic lesions (in the lung and adrenal gland) that exhibited growth during enfortumab vedotin therapy. Immunostaining analysis revealed decreased nectin‐4 expression and elevated MDR1, MRP1, and BCRP expression in the metastatic lesions. Conclusion Decreased nectin‐4 expression and increased ATP‐binding cassette transporter expression are potential factors in the development of enfortumab vedotin resistance in urothelial carcinoma. Immunohistochemical evaluation of these proteins may aid in predicting treatment efficacy.